LEGAL PROTECTION MEASURES FOR VICTIMS OF BPOM BARCODE COUNTERFEITING ON SKINCARE PRODUCT PACKAGING: A REVIEW FROM THE PERSPECTIVE OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Romadon Nasution; Syofiaty Lubis (Journal Analytica Islamica, 2026)
The falsification of barcodes or notification numbers issued by the Indonesian Food and Drug Authority (BPOM) on skincare product packaging constitutes the dissemination of misleading information that may cause economic losses and endanger consumer health. This study aims to analyze the legal status of falsified marketing authorization information and the forms of legal protection available to consumers under Law Number 8 of 1999 on Consumer Protection and BPOM regulations. The study employs a normative legal method using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively and prescriptively using grammatical, systematic, and teleological interpretation. The findings demonstrate that the falsification of notification numbers violates consumers’ rights to safety and accurate information, as well as business actors’ obligation to act in good faith. Preventive protection includes product notification, market surveillance, accurate labeling, legality verification, and consumer education. Repressive protection comprises product recalls, sanctions, complaint mechanisms, dispute resolution, and compensation. However, victim protection remains fragmented across product supervision, law enforcement, and loss-recovery mechanisms, particularly in digital commerce. Therefore, an integrated marketing authorization verification system, stronger accountability of digital platforms, improved inter-agency coordination, and accessible complaint and compensation mechanisms are required.